2018
DOI: 10.1128/mbio.00225-18
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Upc2p-Inducible ERG3 Transcription Is Sufficient To Confer Niche-Specific Azole Resistance without Compromising Candida albicans Pathogenicity

Abstract: Inactivation of sterol Δ5,6-desaturase (Erg3p) in the prevalent fungal pathogen Candida albicans is one of several mechanisms that can confer resistance to the azole antifungal drugs. However, loss of Erg3p activity is also associated with deficiencies in stress tolerance, invasive hyphal growth, and attenuated virulence in a mouse model of disseminated infection. This may explain why relatively few erg3-deficient strains have been reported among azole-resistant clinical isolates. In this study, we examined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 54 publications
1
27
0
Order By: Relevance
“…an inability to cause lethality), an erg3Δ/Δ deletion mutant was relatively resistant to fluconazole treatment in a mouse model of disseminated infection, as treatment did not significantly reduce levels of erg3Δ/Δ colonization of kidney tissue. Strikingly, in a mouse model of vaginal candidiasis, the erg3Δ/Δ mutant not only was able to readily colonize and to induce pathology but also was resistant to fluconazole treatment (18). These findings clearly confirm that loss of Erg3p activity does result in azole resistance within the mammalian host, although it also results in niche or context-specific defects in pathogenicity.…”
Section: Figmentioning
confidence: 54%
See 3 more Smart Citations
“…an inability to cause lethality), an erg3Δ/Δ deletion mutant was relatively resistant to fluconazole treatment in a mouse model of disseminated infection, as treatment did not significantly reduce levels of erg3Δ/Δ colonization of kidney tissue. Strikingly, in a mouse model of vaginal candidiasis, the erg3Δ/Δ mutant not only was able to readily colonize and to induce pathology but also was resistant to fluconazole treatment (18). These findings clearly confirm that loss of Erg3p activity does result in azole resistance within the mammalian host, although it also results in niche or context-specific defects in pathogenicity.…”
Section: Figmentioning
confidence: 54%
“…A C. albicans erg3⌬/⌬ mutant exhibits characteristics of both azole resistance and trailing growth. In this study, we used a previously reported C. albicans erg3Δ/Δ mutant and its isogenic control strain, in which a wild-type (WT) copy of ERG3 has been reintroduced (18). These strains were compared with the well-characterized azoleresistant clinical isolate TW17, which overexpresses the Mdr1p and Cdr1p efflux pumps, as well as a variant of the target enzyme Erg11p with reduced affinity for azoles (4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The two front-line antifungals in clinical use against mucormycosis are the azole isavuconazole and the polyene amphotericin B. Resistance to azoles and polyenes in other pathogenic fungi, such as Candida species, can be mediated by loss of the ergosterol biosynthetic enzymes Erg3and Erg6[47][48][49][50][51][52]. Using bioinformatic analysis we have identified three candidate ERG6 homologs and one candidate ERG3 homolog in Mucor and we hypothesize that epimutation could induce silencing of these genes under appropriate drug selection, leading to acquired drug resistance.…”
mentioning
confidence: 99%